TEMBANG DAN MODEL PENGAJARANNYA - Bambang Sulanjari (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2011)
The major of Tembang is a small partof theconstellation ofthe Java languagecurriculum that included in theclumps. Due toaless strategicposition, thismajor is often overlooked,butiffurtherexplored,this major is so potentialtodevelop thecharacterof students. At least, tembang can be utilizedmosteffectivelytodevelop thefourlanguage skills: listening, reading, writingand speaking.Competenciescan be developedin thetembanglearningof them arethe studentsable tosing thesong, phrasing thesongandmakesong.Learningmodel selectionis crucial in thesuccess oftembanglearning. Creativityof teachersin selectingandimplementinglearning modelis very influentialon the success oftembanglearning, therefore teachersmust be creativeto determine the modelaccordingto the circumstances. In terms ofsongselection ofteaching methods, teachers can developmethods that areinheritedancestors, such asmethods of learningwith playing, the method of learningwith moving, step bystepmethod, andkaraoke method.